THE VALUE GAP: DISCREPANCY BETWEEN NORMATIVE IDEALS AND INDIVIDUAL PRIORITIES IN ENVIRONMENTAL ETHICS (Web of Teachers: Inderscience Research, 2026)
Environmental ethics, as an academic and philosophical discipline, strives to articulate the values, principles, and responsibilities that should govern human interaction with the natural world. A key focus within this field is the formulation of normative ideals—standards or aspirations that direct how individuals and societies ought to treat their environment. Notably, these ideals commonly emphasize sustainability, stewardship, respect for non-human life, and the minimization of harm to natural systems. However, the translation of these widely acknowledged or even legally encoded values into personal motivations, decisions, and behaviors is complex and often incomplete. This incongruence between collective, normative environmental ideals and the everyday priorities guiding individual conduct is often described as the “value gap.”